Transforming the Role of the Clinical Faculty Coordinator in the Dedicated Education Unit. Issue 6 (November 2018) - Auxier, Nicole; Simpson, Holly
Abstract : Abstract: The dedicated education unit (DEU) clinical education model has been identified nationally as an innovative model for clinical nursing education. This article identifies the core values of the DEU clinical faculty coordinator role and describes the transformation of this role across three clinical models. The role has been adapted to fit the needs of acute care, post-acute care, and community nursing DEU models, meeting the needs of the clinical educational environment and clinical staff as well as student learning outcomes.